Comparative survival and growth performance of European lobster Homarus gammarus post‐larva reared on novel feeds. (11th October 2019) - Hinchcliffe, James; Powell, Adam; Langeland, Markus; Vidakovic, Aleksandar; Undeland, Ingrid; Sundell, Kristina; Eriksson, Susanne P.
Abstract: One approach to ongrow juvenile European lobster, Homarus gammarus, is to utilize land based rearing systems, incorporating automated feeding, individual culture and provision of stable pelleted feeds, preferably using sustainable ingredients. We initiated three feeding experiments to investigate the general suitability of ingredients produced from seafood by‐products as novel feeds for H. gammarus, in terms of promoting survival, development and growth of post‐larval lobsters from post‐larvae (PL) stage IV to the first juvenile stage (stage V). The first experiment was designed to screen an array of candidate, locally produced, novel protein sources on growth performance parameters. This initial experiment revealed that PL reared on a raw (i.e. wet, unprocessed shrimp) feed used as a reference showed superior performance to those reared on experimental feeds containing fishmeal, herring protein isolate or mussel meal; however, a novel type of shrimp meal, produced by flocculation from waste water, promoted the best PL performance of any experimental feed. A second experiment was designed to test the effect of drying method and to optimize the form of a wet shrimp reference feed used by lobster hatcheries. This showed that the performance of PL reared on experimental freeze‐dried shrimp feed was not significantly different to those reared on the wet, unprocessed shrimp used as a reference feed. However, lobsters offered experimental oven‐dried shrimp feed (with or without an immune supplement) resulted in significantly lower survival or growth performance. A third and final experiment was designed in an attempt to improve a candidate herring‐based protein source, by supplementing with nutrients found in shrimp. However, the results showed that PL reared on the wet reference shrimp feed still showed superior growth and survival than those reared on a herring feed alone, or supplemented with additives found in shrimp meal (either glucosamine, astaxanthin or both supplements combined). The high survival and growth, low incidence of moulting problems and high availability of waste shrimp material, suggest that non‐heat‐treated shrimp products are a promising feed ingredient for post‐larval European lobsters.